Fashioning Identity: A Technocultural Analysis of Igbo Women Designers’ Self-Presentation on Instagram - Joy C. Enyinnaya (Social Media + Society)
Using African Technocultural Feminist Theory (ATFT), this study explored how Nigerian Igbo women fashion designers use Instagram to perform digital identities. While there is extensive literature on self-presentation on social media, there is limited research on African women’s self-presentation from a feminist perspective. The Critical Technocultural Discourse Analysis (CTDA) of Instagram posts and interview data revealed that Instagram’s photo affordances allowed designers to showcase their intricate designs and facilitate the cultural digitization of Igbo-centric fashion. The result of the three-phased analysis revealed Nigerian Igbo women fashion designers employed visual aesthetics and authenticity in their entrepreneurial online presentation. The study also highlighted the reemergence of Nsibidi , a long-lost ideography within Igbo culture, facilitated by Instagram. In addition, the study revealed that Nigerian Igbo women fashion designers use Instagram to challenge societal norms related to femininity and womanhood. This study addresses the need to examine African women’s digital identities through a feminist lens, considering the impact of overlapping power structures on their self-representational choices on social media.